Effect of foamed concrete with egg albumen - Lau, Yih Bing (2010)
In Malaysia, the usage of foamed concrete is widely used in construction of buildings which can reduce the cost and time of project. This study is to investigate the effect of foamed concrete strength with 1% and 5% egg albumen were used. This study was conducted to improve the performance of foamed concrete by using egg albumenwhere egg albumen is considered as an agriculture waste material. The tests conducted in this study were compression strength, flexural strength and drying shrinkage. A total of 54 cubes (150mm x 150mm x 150mm) and 54 prisms (500mm x 100mm x 100mm) were casted according to three different mixtures including control foamed concrete of 1400kg/rn3 density. The samples were cured under two curing conditions which were air and water curing for 7, 14 and 28 days before testing. Three types of mixtures were cast based on 1% egg albumen foamed concrete (1% EAFC), 5% egg albumen foamed concrete (5% EAFC) and 100% foamed concrete (100% FC). The result for 1% EAFC mixture in air curing shows 30% higher compressive strength and 90% higher flexural strength with increase density when compared with control foamed concrete at 28th days while compressive and flexural strength in water curing was 84% and 80% higher. As for 5% EAFC, it consists of unstable compressive strength and higher flexural strength with increase density when compared with control foamed concrete which was 64% and 35% higher for air curing while compressive and flexural strength in water curing was 19% and 14% higher at 28th days. Water curing for 100% FC and 1% EAFC mixtures has higher compressive and flexural strength compared to air curing while 5% EAFC is vice versa. Shrinkage value for 100% FC and 1% EAFC are more stable while shrinkage value for 5% EAFC is not consistent. The significant of this study is to produce a lightweight concrete with waste material which is more environment friendly and improved properties.